Epigenetic regulation of human papillomavirus transcription in the productive virus life cycle - Burley, Megan (Semin Immunopathol, 2020)
Human papillomaviruses (HPV) are a large family of viruses which contain a circular, double-stranded DNA genome of approximately 8000 base pairs. The viral DNA is chromatinized by the recruitment of cellular histones which are subject to host cell–mediated post-translational epigenetic modification recognized as an important mechanism of virus transcription regulation. The HPV life cycle is dependent on the terminal differentiation of the target cell within epithelia—the keratinocyte. The virus life cycle begins in the undifferentiated basal compartment of epithelia where the viral chromatin is maintained in an epigenetically repressed state, stabilized by distal chromatin interactions between the viral enhancer and early gene region. Migration of the infected keratinocyte towards the surface of the epithelium induces cellular differentiation which disrupts chromatin looping and stimulates epigenetic remodelling of the viral chromatin. These epigenetic changes result in enhanced virus transcription and activation of the virus late promoter facilitating transcription of the viral capsid proteins. In this review article, we discuss the complexity of virus- and host-cell-mediated epigenetic regulation of virus transcription with a specific focus on differentiation-dependent remodelling of viral chromatin during the HPV life cycle.